THE SEMBEQ SENGGETENG RITUAL PRACTICE AND ITS EFFECT ON THE DECLINE OF AN EARLY AGE MARRIAGE IN LOMBOK - Hamdi, Saipul; Awalia, Hafizah; M. Irman Zuhdi; Riduan, Imam Malik (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2025)
The sembeq senggeteng is a unique rite that bind young people's hearts so that they do not marry too early. The ritual was established by the native ancestor of East Lombok people, especially those in Lekor village. The ritual is complicated in terms of the symbolic value of the offerings material. As a result, this study looks into the process of performing ritual, the symbolic meanings of the presenting element, and the influence on preventing early marriage. The study adopted a qualitative method and a phenomenological approach. The research revealed that each procedure of the ceremony and its offering has a symbolic value, such as betel leaves as a substitute for skin, areca nut for the heart, lime for bones, rice for meat, and thread for veins. This ritual has a significant impact on avoiding early marriage in this hamlet, and the government should implement the ritual to lower the number of early marriages in Lombok.